A new perspective on sin in the age of globalisation: Analyses and reflections of sin in the case of nation-state building of the United States - Kwak, Ho Chul (HTS teologiese studies, 2021)
An interconnected and interdependent world in the age of globalisation invites Christianity to a different understanding of sin, which has been individualistically understood, because individualistic understanding of sin is impotent to address injustice or oppression caused by collective sins, wherein human beings have been collectively involved in. In order to overcome individualistic understanding of sin, this article is critically engaged in the concepts, such as concrete totality, which sees both individuality and socialness as constitutive parts of human beings, tyranny of collective identity through which oppression and injustice is carried out to unspecified others and retreat from truth to omnipotence, which is a concretised example of tyranny of collective identity in a nation-state building of the United States. Retreat from truth to omnipotence means that the United States covers its blamable history with relation to Native Americans and immigrants and justifies the discrimination and exclusion of others using untrue social, political, hygienic and economic reasons. Retreat from truth to omnipotence is not a temporal aberration but a constant repetition in the US history. To address discrimination and exclusion of others necessitates a new understanding of sin, that is, sin of human beings as concrete totality rather than an exclusively individualistic view of sin.Contribution: The article explores a necessity of emphasizing collective dimension of sin to address injustice and oppression caused by tyranny of collective identity in a globalizing world. It provides a theological foundation for building a welcoming political community to immigrants who have been unjustly discriminated or excluded.